2012 International Symposium on Electronic System Design (ISED) 2012
DOI: 10.1109/ised.2012.66
|View full text |Cite
|
Sign up to set email alerts
|

e-SURAKSHAK: A Cyber-Physical Healthcare System with Service Oriented Architecture

Abstract: In this paper we present the design of "e-SURAKSHAK," a novel cyber-physical health care management system of Wireless Embedded Internet Devices (WEIDs) that sense vital health parameters. The system is capable of sensing body temperature, heart rate, oxygen saturation level and also allows noninvasive blood pressure (NIBP) measurement. End to end internet connectivity is provided by using 6LoWPAN based wireless network that uses the 802.15.4 radio. A service oriented architecture (SOA) [1] is implemented to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Furthermore, Rao et al [ 16 ] showed e-SURAKSHAK, which was a novel cyber-physical healthcare system with service oriented architecture. The authors developed their own monitoring system that allowed measuring body temperature, heart rate, oxygen saturation level, and noninvasive blood pressure measurement.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, Rao et al [ 16 ] showed e-SURAKSHAK, which was a novel cyber-physical healthcare system with service oriented architecture. The authors developed their own monitoring system that allowed measuring body temperature, heart rate, oxygen saturation level, and noninvasive blood pressure measurement.…”
Section: Related Workmentioning
confidence: 99%
“…Rao et al [ 32 ] presented “e-SURAKSHAK”, a health care management system that sense vital health parameters. The sensed health parameters are communicated to a centralized electronic database wirelessly.…”
Section: Revised Soa Applicationsmentioning
confidence: 99%
“…Computer parts are becoming increasingly more high-capacity at lower power consumption and smaller form-factors. As a result, the CPS is also becoming more and more demanding in the fields of aerospace [5,10], defense [11,12], energy systems [13,14], healthcare [3,[15][16][17][18], transportation [19][20][21][22][23], and others [24][25][26].…”
Section: What Is Cps?mentioning
confidence: 99%